2020
DOI: 10.12701/yujm.2020.00038
|View full text |Cite
|
Sign up to set email alerts
|

Jejunogastric intussusception prone to misdiagnosis as gastric cancer

Abstract: The authors report a case of a 78-year-old female with a history of gastric surgery 35 years ago. She was initially misdiagnosed as gastric cancer bleeding and underwent an emergency laparotomy under the diagnosis of jejunogastric intussusception (JGI), 23 hours after the onset of symptoms. We also reviewed 116 JGI case reports and analyzed clinical features and outcomes. Compared to the past, diagnosis of JGI is easier with diagnostic examinations such as an endoscopy, computed tomography, and the upper gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
(15 reference statements)
1
1
0
Order By: Relevance
“…In the diagnosis of JGI, medical history of surgery and contrast-enhanced CT scan are essential. Alike previously reported [ 6 , 12 ], the CT scan also showed that jejunal loop invaginated into remnant stomach accompanying its mesentery and mesenteric vessels. If patient’s general condition allows, gastroscopy is more useful to make an accurate diagnosis of JGI, revealing a so-called ‘green caterpillar-like’ lesion [ 13 ], a mass with mucosal folds protruding through anastomosis.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In the diagnosis of JGI, medical history of surgery and contrast-enhanced CT scan are essential. Alike previously reported [ 6 , 12 ], the CT scan also showed that jejunal loop invaginated into remnant stomach accompanying its mesentery and mesenteric vessels. If patient’s general condition allows, gastroscopy is more useful to make an accurate diagnosis of JGI, revealing a so-called ‘green caterpillar-like’ lesion [ 13 ], a mass with mucosal folds protruding through anastomosis.…”
Section: Discussionsupporting
confidence: 76%
“…Although emergency surgery is the standard treatment, endoscopic reduction has also been reported to be effective in JGI patients without bowel necrosis [ 2 ]. However, several early recurrent cases treated with surgical or endoscopic reduction have been reported [ 3 6 ]. We report an extremely rare case of JGI after pancreaticoduodenectomy (PD) using the Child’s procedure that was successfully treated with surgical reduction and fixation.…”
Section: Introductionmentioning
confidence: 99%